Osteosynthesis of intercondylar humerus fracture using Bryan and Morrey approach - Lakhey, S; Sharma, S; Pradhan, RL; Pandey, BK; Manandhar, RR; Rijal, KP (Kathmandu University Medical Journal, 2010)
Background: The olecranon approach has been the gold standard for surgical approaches to fracture fixation of distal articular surface of humerus. Although it provides a good exposure, it also has disadvantages of delayed union, nonunion and implant related complications at the osteotomy site. Objective: The aim of this study was to determine the functional outcome of displaced intra-articular distal humerus fracture fixation using an alternative approach: the Bryan and Morrey approach. Materials and methods: Twenty patients with twenty AO type C1 and C2 intercondylar fractures of the distal humerus had bicolumnar fixation of the distal humerus with two contoured reconstruction plates and screws on the dorsal surface or various combinations of a single reconstruction plate, screws and K-wires using a Bryan and Morrey approach. Twelve of the patients were male and eight were female. The average age of the patients was 44.8 years. Eleven patients had sustained the injury as result of fall and nine of the patients had sustained it in road traffic accidents. Right elbow was involved in fifteen patients and left in five. All patients were followed up for 12 months post operatively. Results: All twenty fractures had united at 4 months follow-up. The mean fixed flexion deformity was 9.0° (range 0°-15°) and the mean arc of motion was 115.0° (range 85°-130°). All patients had grade 4 triceps strength and stable elbows at the end of 12 months follow up. One patient had deep seated wound infection resulting in necrosis of the triceps tendon requiring a second operative procedure. Conclusions: Bryan and Morrey approach is a simpler, easier and better approach as compared to the other posterior approaches to the elbow joint, and therefore, can be used as the approach of choice for fixation of fractures of the distal articular surface of humerus. Key words: Fracture; Intercondylar Humerus; Osteosynthesis DOI: 10.3126/kumj.v8i2.3549 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 154-157